Reformulation of Customary Criminal Law in the National Criminal Code Based on the Formation of Legislation - Muhammad Junaidi; Yoghi Arief Susanto (Jurnal Pembangunan Hukum Indonesia, 2025)
Customary criminal law, as a living law in society, holds a recognized position as an unwritten source of law. However, Article 2, Paragraph (3) of Law No. 1 of 2023 concerning the Criminal Code (KUHP) stipulates that customary law must be established through government regulations. This requirement poses a challenge and introduces new complexities in the reform of the National Criminal Code.This study aims to reconceptualize customary criminal law within the National Criminal Code based on the framework of statutory formation. The research adopts a doctrinal approach with a normative juridical method, utilizing legal sources such as legislation, jurisprudence, court decisions, and academic literature through a literature review. The analysis is conducted qualitatively.The findings reveal that customary criminal law already holds an equivalent position to statutory law and jurisprudence as an unwritten source of law. Therefore, formalizing customary law in the form of regional regulations is misguided. The application and procedural aspects of customary law should remain under the authority of indigenous communities. Meanwhile, the imposition of additional sanctions by judges should be regulated in the revised Criminal Procedure Code while respecting customary community norms.In conclusion, customary criminal law holds an equal position as an unwritten legal source and should remain recognized without requiring formalization through regional regulations. The state's role should be limited to providing protection and acknowledgment rather than enforcing formalization.